Functional Model of Improving the Treasury System in Budget Execution - Mansur Alisherovich Mansurov (Zien Journals, 2022)
This scientific article scrutinizes the enlargement of the treasury system of budget execution as an essential element of the stability of the entire financial system of the country. The importance of continuous improvement and modernization of the work of treasury bodies is emphasized, which will significantly reduce transaction costs in the budgetary sphere and, accordingly, increase the level of efficiency of budget execution in the medium term of the Republic of Uzbekistan.
Keywords: Budget; execution; functional model; improvement